EXPLORING THE IMPACT OF SUSTAINABLE MARKETING ON CONSUMER PURCHASE DECISIONS: A COMPREHENSIVE LITERATURE REVIEW - Dhingra, Arti; Rani, Barkha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper investigates the influence of sustainable marketing strategies, such as eco-labeling, green packaging, and corporate social responsibility (CSR), on consumer purchase decisions, using secondary data. Drawing from a comprehensive review of existing literature, the study explores how consumer trust and brand loyalty mediate the relationship between sustainable marketing initiatives and purchase intentions. Key findings indicate that sustainable marketing practices significantly shape consumer behavior, leading to positive purchase decisions and fostering long-term loyalty when trust is established. Additionally, CSR and green marketing efforts provide brands with a competitive advantage, allowing them to differentiate in increasingly eco-conscious markets. The paper concludes with practical implications for marketers, businesses, and policymakers, and suggestions for future research on demographic variations, digital marketing, and industry-specific sustainability approaches. Overall, this study provides valuable insights for both academia and industry practitioners, highlighting the critical role of sustainable marketing in influencing consumer behaviour and promoting long-term brand loyalty. By adopting strategic, transparent, and innovative approaches to sustainability, businesses can not only meet the rising consumer demand for eco-friendly products but also contribute to a more sustainable and responsible global marketplace.